The Effectiveness of Comic Strip–Based Learning Media in Enhancing Students’ Learning Outcomes on Rukhsah in Islamic Education: A Quasi-Experimental Study - Putri, Resy Retna; Wirdati (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the effectiveness of comic strip–based learning media in enhancing students’ learning outcomes on the topic of rukhsah in Islamic Education. The research is motivated by the persistent challenges in teaching abstract religious concepts using conventional instructional methods, which often result in low student engagement and limited conceptual understanding. This study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group. The sample consisted of 56 eighth-grade students from SMPN 42 Padang, divided into an experimental group and a control group. Data were collected through pretest and posttest assessments, observation sheets, and documentation. The instruments were validated through expert judgment and reliability testing. Data analysis was conducted using descriptive and inferential statistics, including normality and homogeneity tests, independent samples t-test, and N-Gain analysis. The results revealed a significant improvement in students’ learning outcomes in the experimental group compared to the control group. The mean score increased from 64.75 (pretest) to 90.43 (posttest) in the experimental group, while the control group improved from 64.07 to 81.96. The independent samples t-test showed a significance value of 0.001 (< 0.05), indicating a statistically significant difference between the two groups. Furthermore, the N-Gain score of 77.58% in the experimental group was categorized as highly effective, confirming that comic strip–based learning media substantially enhances students’ understanding of rukhsah. This study offers a novel contribution by integrating comic strip–based visual narrative media into the teaching of Islamic jurisprudential concepts, particularly rukhsah, which has rarely been explored through rigorous quasi-experimental research. It introduces a contextual visual learning approach that bridges abstract religious knowledge with real-life situations. The study contributes theoretically by supporting the Cognitive Theory of Multimedia Learning and constructivist learning principles within Islamic Education. Practically, it provides an innovative instructional strategy for educators to improve student engagement and conceptual understanding. Additionally, it offers empirical evidence that can inform curriculum development and the integration of creative learning media in religious education.